TC2015: Life cycle analysis of co‐formed coal fines and hydrochar produced in twin‐screw extruder (TSE) - Liu, Xiaowei (Vivian); Hoekman, S. Kent; Farthing, William; Felix, Larry (Environmental progress & sustainable energy, 2017)
Life cycle analysis (LCA) is a quantitative tool that evaluates the environmental performance of a process or system. The main objective of this LCA study is to assess the greenhouse gas (GHG) emissions and life cycle energy use associated with solid fuels produced by co‐forming coal fines and hydrochar. The hydrochar is derived from loblolly pine wood via hydrothermal carbonization (HTC) conducted in a reactive twin‐screw extruder (TSE). The final product is a drop‐in replacement for coal. The life cycle impacts of the co‐formed end products are quantified from ‘cradle‐to‐grave’. Model input parameters are collected from life cycle databases, literature, experimental measurements and simulations by engineering software. Results show that electricity generated from the co‐formed products has significantly lower GHG intensity and slightly higher life cycle energy use than coal‐generated electricity. The most carbon‐intensive component in the overall hydrochar system is the HTC plant. However, this could be improved in the future by plant re‐design to recover and recycle thermal energy for more efficient operation. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 668–676, 2017